امام خطابیؒ کی ’’اصلاح غلط المحدثین‘‘ (تعارف، منہج واسلوب اور امتیازی خصائص): Iṣlāḥ ghalaṭ al-muḥaddithīn by Abu Sulayman Hamd Ibn Muhammed al-Khattabi: Introduction, Style & Methodology and Characteristics - Shahzada Imran Ayub; Dr. Muhammad Ijaz (MEI, 2023)
Imam Khattabi is related to the fourth century. He has written several books in various sciences. One of them an important book is "Islah Ghalat al-Muhaddiseen". In this book, he has written about 143 Ahadith under various titles and under these Ahadith he interpreted 160 words. In this regard, Initially, he mentions the correct words of the Hadith, then he mentions the misktake of some of the narrators and then He correctes it. As a inference, he has mentioned many Ayaat, Ahadith, verses and sayings of muhaddiseen in many places. In some places he also mentioned the Unique events of some mohaddiseen. It is also a discrimination feature of this book that he mentioned the verses and sayings of scholars with his own chain. Due to these qualities of the book, many mohaddiseen have also copied the quote in their own books in which Imam Ibn Aseer, Imam Nwawi, Qazi Ayaaz and Hafiz Ibn Hajar Asqlani are remarkable.